Chemicals Identification Related To The Chemical Weapons Convention During The 15th Interlabory Proficiency Test - Sri Sumartini; Harry Budiman; Nuryatini Nuryatini; Puspa Dewi (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2008)
Identification of some chemical weapons in the water and organic sample has been carried out during 15th proficiency testing hold by OPCW (Organisation Prohibition of Chemical Weapon). Sample preparation method was adopted from Recommended Operational Procedure (ROP) from OPCW and Helsinki University, Finlandia. Prepared sample was identified by gas chromatography (FID and FPD), gas chromatography mass spectrometry (EI and CI mode) and Liquid chromatography mass spectrometry method.. From 7 spiking chemical weapons introduced to water and organic sample, 3 spiking chemicals could be identified (propylphosphonic acid, isoprophylphosphonic acid and 1,4 Bis 2-chloroethyl (thio) butane). One chemical was reported as Butyl S-2-diisopropylaminoethyl propylphosphonothiolate but obviously this is not a spiking chemical (category false positive identification).